Upaya Meningkatkan Hasil Belajar Melalui Model Pembelajaran Listening Team Mata Pelajaran Sejarah Kebudayaan Islam Siswa Kelas VIII MTs Swasta Tarbiyah Waladiyah Pulau Banyak Kecamatan Tanjung Pura Kabupaten Langkat - Muhammad Saleh; Ahmad Zaki; Sri Agustina (Continuous Education: Journal of Science and Research, 2022)
The objectives of this study are to determine the application of the listening team learning model at MTs Swasta Tarbiyah Waladiyah Pulau Banyak, to improve learning outcomes of Islamic Cultural History subjects in class VIII MTs Private Tarbiyah Waladiyah Pulau Banyak, to find out if there are any improving student learning outcomes through the listening team learning model for the subjects of Islamic Cultural History Class VIII MTs Swasta Tarbiyah Waladiyah Pulau Banyak. The model in this study uses Kurt Lewin's research model which consists of 4 stages, namely; planning, implementing actions, observing and reflecting. The subject of this research is the eighth grade students of MTs Swasta Tarbiyah Waladiyah Pulau Banyak. Which consists of 35 students. Data collection techniques using interviews, observation, documentation, and written test assessment. Before using the listening team learning model, the teacher still uses the conventional model, namely by using the lecture method in learning. So that students are not interested in understanding the learning material and this is very influential on student learning outcomes, namely only 33% of students who completed when I did the pre-test and 77% of students did not complete. From the observations, it was shown that students' responses to the use of the jigsaw learning model in learning showed a positive and enthusiastic attitude, all aspects had been met. The use of the listening team learning model can improve student learning outcomes from pre-cycle students who complete 33% of cycle I students who complete 62% of student mastery increases by about 29%, cycle II students who complete about 100%, from cycle I to cycle II students completeness increases about 38%. With this, the Jisaw learning model has succeeded in improving the learning outcomes of SKI subjects in class VIII MTs Swasta Tarbiyah Waladiyah Pulau Banyak.